Interactions between root endophytic microorganisms and the reduced negative ion release capacity of Phalaenopsis aphrodite Rchb. f. under high temperature stress - Ye, Qi; Lv, Wenzhuo; Lu, Yin; Wei, Zili; Guo, Yunxin; Wang, Peijie; Sun, Bingru; Tong, Yumei; Xuan, Shenke; Lin, Wei; Guo, Lijin (Frontiers in Plant Science, 2024)
Introduction Negative oxygen ions are produced by plants through photosynthesis, utilizing "tip discharge" or the photoelectric effect, which has various functions such as sterilization, dust removal, and delaying aging. With global warming, high temperatures may affect the ability of Phalaenopsis aphrodite Rchb. f. to produce negative oxygen ions. P. aphrodite is commonly used in modern landscape planning and forest greening. Methods In this study, P. aphrodite was selected as the research object. By artificially simulating the climate, the control group (CK) and the high temperature stress group (HS) were set up in the experiment. Results The study found that compared with the control group, the ability of P. aphrodite to produce negative oxygen ions significantly decreased when exposed to high temperature stress. Meanwhile, under high temperature stress treatment, peroxidase content increased by 102%, and proline content significantly increased by 35%. Discussion Redundancy analysis results indicated a significant correlation between the root endophytic microbial community of P. aphrodite and negative oxygen ions, as well as physiological indicators. Under high temperature stress, P. aphrodite may affect the regulation of physiological indicators by modifying the composition of root endophytic microbial communities, thereby influencing the ability to release negative oxygen ions.